PELATIHAN PENGGUNAAN MICROSOFT WORD UNTUK MENINGKATKAN HARD SKILL DAN SOFT SKILL WARGA BELAJAR PAKET C DI PKBM JAYAGIRI LEMBANG - Salsa Billa; Asep Samsudin; Asep Kustiana (IKIP Siliwangi, 2026)
This study aims to determine the improvement of hard skills and soft skills of Package C learners at PKBM through a Microsoft Word training program organized by the researcher. The research method used was an experimental design with a one group pretest-posttest approach. The research subjects consisted of 16 learners from the Package C program. Research instruments included questionnaires, observation sheets, and skill tests to measure participants’ improvement. The results showed a significant increase in both hard skills and soft skills after the training. This was evidenced by the paired sample t-test results, which indicated a significance value of < 0.05, meaning that the training had a positive effect on skill enhancement. Furthermore, the coefficient of determination test and simple regression analysis also confirmed that the training contributed to the improvement of learners’ skills. In conclusion, the Microsoft Word training, designed in a practical manner and tailored to participants’ needs, had a positive impact on improving both technical skills (hard skills) and non-technical skills (soft skills) of Package C learners.